Online Short-Term Mindfulness-Based Intervention During COVID-19 Quarantine in Italy: Effects on Wellbeing, Stress, and Anxiety - Fazia, Teresa; Bubbico, Francesco; Nova, Andrea; Riggi, Emilia; Caimi, Giancarlo; Calgan, Beril; Salvato, Gerardo; Bruno, Salvatore; Bottini, Gabriella; Bernardinelli, Luisa (Frontiers in Psychology, 2022)
In order to limit the first spread of COVID-19 in March 2020, the Italian government imposed strict lockdown measures to the population. Despite necessary to reduce the virus transmission and the burden to the hospitals, social isolation has caused detrimental effects on psychological well-being and mental health. Moreover, during this period it was also difficult to deliver psychological treatments and psychiatric assistance. A short (a weekly session for 9 weeks) mindfulness-based meditation program, named Integral Meditation (IM), was administered entirely online to healthy adults from Italy. This is a two-groups pre-post quasi experimental study in which the two groups, treated and control were not randomized. Through matching procedures aimed at overcoming the absence of randomization, we analyzed a sample of 84 subjects (42 for each group). By applying linear mixed effect models, we tested the hypothesis of a beneficial effect of IM on well-being, perceived stress and state anxiety, as measured by three self-reported questionnaires (WEMWBS, PSS and STAI-X1 respectively), assuming that this effect could be different according to the level of baseline trait anxiety, as measured by STAI-X2. Results showed a statistically significant effect of STAI-X1 (β=-8.24 [95%CI-15.39;-1.09], p=0.02) and WEMWBS (β=4.61 [95%CI 0.94;8.29], p=0.01) in the higher trait anxiety subgroup only. No statistically significant effect of IM was observed for PSS. These results suggest that our IM, delivered online, may increase mental well-being and decrease anxiety specifically in subjects with higher trait anxiety.